Multicultural Education Management Reform with Religious Approach, Da'wah, and Technology in MuhammadiyahHigh School: Tranformasi Managemen Pendidikan Multikultural dengan Pendekatan Religi, Da’wah, dan Teknologi di SMK Muhammadiyah - Joko Trihono; Wisnu Panggah Setiyono (Academia Open, 2020)
This research aims to describe and analyze the school's vision, mission, and values process transformed into multicultural education planning ,Multicultural education implementation process, multicultural education evaluation form. To avoid poisoning in understanding the meaning of the title of this study, it is necessary to explain the intent and meaning of the words composed in the title namely: Education is various efforts made by a person (educator) towards a person (protégé) in order to achieve positive maximum development. Planning is an intellectual process for determining goals and ways of achieving them. Implementation is the process of rationing or making it real in another sense is the process of implementation. Transformations are two main definitions. The first transformation is the fundamental change of organizational elements in adjustment to environmental change. The second is the dialogue process that takes place between teachers and students, students and students as part of the educational process with the aim of developing the skills of students. Management is the science or art of managing a set of tasks through the intermediary of others in achieving goals effectively and efficiently. Multiculturalism is an idea born of the fact of differences between citizens. Different life experiences foster different awareness and values that sometimes appear contradictory. Human encounters of different ethnic backgrounds are increasingly extending across the territorial boundaries of nations and countries to continental boundaries. In this study will discuss how multicultural is interpreted in the lives of citizens. This research will look at the diversity that exists in schools. Multicultural education in this study multicultural education is interpreted as an educational process based on multiculturalism which means acceptance of diversity in life. In relation to how this education will be packaged into multicultural education programs. These programs begin with planning, implementation, and evaluation conducted together.